2019
DOI: 10.1001/jamapediatrics.2019.1212
|View full text |Cite
|
Sign up to set email alerts
|

Association of Team Sports Participation With Long-term Mental Health Outcomes Among Individuals Exposed to Adverse Childhood Experiences

Abstract: IMPORTANCE Adverse childhood experiences (ACEs) are associated with long-term poor mental health. Less is known about factors that improve long-term mental health among those with ACEs. OBJECTIVE To evaluate, among those exposed to ACEs, whether team sports participation during adolescence is associated with better mental health in adulthood and whether the association between team sports participation and mental health varies by sex. DESIGN, SETTING, AND PARTICIPANTS This study used data from 9668 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 37 publications
3
81
0
Order By: Relevance
“…1,2 High school athletics play an important role in improving the short-and long-term health of these students. [3][4][5][6][7][8][9][10] During the winter and spring of 2020, the novel SARS-CoV-2 coronavirus and the resultant disease, COVID-19, reached pandemic proportions in the United States. In an effort to slow the spread of COVID-19, high schools across the US were closed to in-person teaching, and many extracurricular activities such as high school interscholastic sports were cancelled.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 High school athletics play an important role in improving the short-and long-term health of these students. [3][4][5][6][7][8][9][10] During the winter and spring of 2020, the novel SARS-CoV-2 coronavirus and the resultant disease, COVID-19, reached pandemic proportions in the United States. In an effort to slow the spread of COVID-19, high schools across the US were closed to in-person teaching, and many extracurricular activities such as high school interscholastic sports were cancelled.…”
Section: Introductionmentioning
confidence: 99%
“…However, specific outcomes vary by activity type, with research consistently showing that sport participation may have long-term mental health benefits [11,42,70]. Among individuals with a history of adverse childhood experiences, team-sport participation in adolescence has been related to increased resilience against later internalizing disorders in adulthood [24]. Physical activity also has been associated with improvement in depressive symptoms in adolescents aged 13-17 [16].…”
mentioning
confidence: 99%
“…However, there is evidence in the literature that lack of physical activity may be linked to the state of emotional dysregulation known to be associated with obesity [8,48]. Emerging evidence emphasizing the positive role of team sport participation on longer term mental health, especially in children who have experienced adverse childhood events [56] makes this an important consideration in youth such as those in this study. This study found no statistically significant differences in the dietary intake of foods shown to be related to risk of obesity including the servings of water, sugar sweetened beverages, fruits and vegetables, as well as the patterns of meals eaten at home and fast food intake.…”
Section: Discussionmentioning
confidence: 95%